LARVAE OF CADDISFLIES (INSECTA: TRICHOPTERA) FROM THE MESOZOIC OF SIBERIA - Ivanov V.D. (My University, 2006)
Body fossils of caddisfly larvae are described for the first time based on material from the Lower Cretaceous of Siberia (Baissa locality, Neocomian). The material includes a fully grown larva of Baissoplectrum separatum gen. et sp. nov. (Brachycentridae), Creterotesis coprolithica gen. et sp. nov. (Leptoceridae), and Cretolype minuta gen. et sp. nov., a tiny larva probably belonging to an uncertain family of the suborder Annulipalpia (Hydropsychina). C. coprolithica built unusually soft larval cases of pellets; these cases are described as a separate new indusigenus and indusispecies Coprindusia pallida gen. et sp. nov. Bionomics, taxonomy, and evolution of the Mesozoic larvae of Trichoptera are discussed. © Pleiades Publishing, Inc. 2006.
Keywords: Mesozoic; Cretaceous; Mesozoic; Мезозой; Mesozoic::Cretaceous; Мезозой::Меловая